2021
DOI: 10.3389/fpubh.2021.648278
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Socio-Demographic Factors in the Coverage of Breast Cancer Screening: Insights From a Quantile Regression Analysis

Abstract: Background: In Flanders, breast cancer (BC) screening is performed in a population-based breast cancer screening program (BCSP), as well as in an opportunistic setting. Women with different socio-demographic characteristics are not equally covered by BC screening.Objective: To evaluate the role of socio-demographic characteristics on the lowest 10th and highest 90th quantile levels of BC screening coverage.Methods: The 2017 neighborhood-level coverage rates of 8,690 neighborhoods with women aged 50–69 and elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
4
2
0
Order By: Relevance
“…We found the percentage of foreigners to be associated with a lower probability of screening for CRC and BC. These findings are consistent with previous observations at both municipal and individual levels [17,24,25] and can be explained by the reported perceived language barriers and embarrassment when talking about screening [26]. Moreover, migrants are a high-risk group for limited health literacy.…”
Section: Discussionsupporting
confidence: 91%
“…We found the percentage of foreigners to be associated with a lower probability of screening for CRC and BC. These findings are consistent with previous observations at both municipal and individual levels [17,24,25] and can be explained by the reported perceived language barriers and embarrassment when talking about screening [26]. Moreover, migrants are a high-risk group for limited health literacy.…”
Section: Discussionsupporting
confidence: 91%
“…Second, with the exception of age, the other independent variables were measured for the complete municipality population and used as a proxy for the communal target population. Despite the limitations, our results substantiate previous findings at both municipal [17], [18], [24], [25], [29] and individual [26] level.…”
Section: Discussionsupporting
confidence: 89%
“…We found that percentages of people with non-Belgian/Dutch nationality and diabetes are associated with a lower probability of screening for CRC (more chances of being in Group 2 vs. Group 1) and BC (more chances of being in Group 3 vs. Group 1). With regards to foreign nationality, these findings are consistent with previous observations at both municipal and individual level [17], [24], [25] and can be explained by the reported perceived language barriers and embarrassment when talking about screening [26]. Moreover, migrants are a high-risk group for limited health literacy and may experience higher difficulties, compared to non-immigrant individuals, in processing health information and translating them it into healthy behaviors [27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Socioeconomic inequalities in breast cancer screening uptake have been shown to be higher in countries which do not have a nationwide population-based screening program (1,2). However, country-specific studies have brought mixed evidence on screening programs' potential to reduce inequalities in mammography uptake (3)(4)(5)(6)(7)(8). This is the case of Switzerland where regional mammography programs were not found to importantly moderate socioeconomic inequalities in screening uptake (9).…”
Section: Introductionmentioning
confidence: 99%